Safe and correct use of herbicides - Africa Rice Center (Africa Rice Center, 2013)
Weeds are important constraints for rice production. Effective weed management can increase yields by more than 50%, but usually takes a lot of time. As a farmer it is therefore worthwhile investing in labor-saving weed management tools. One such labor-saving method is the use of herbicides, but if these herbicides are not applied in the right way, they may harm the crop, the human health and the environment. In this video, one can learn how to control weeds in lowland rice using herbicides in a safe and efficient way. For more information, please contact Jonne Rodenburg (j.rodenburg@cgiar.org)